DEVELOPING FUN THINKERS BOOK LEARNING MEDIA ON THE TOPIC OF PERISTIWA ALAM YANG TERJADI DI INDONESIA AT GRADE V OF ELEMENTARY SCHOOL - Mariatul Kibtiah; Nana Hendracipta; Encep Andriana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to develop fun thinkers book learning media on the topic of “Peristiwa alam yang terjadi di Indonesia” for grade V elementary school students and to determine the feasibility of the learning media. This research was research and development involving six steps: (1) problem analysis, (2) data information collection, (3) product design, (4) design validation, (5) product revision, and (6) product testing. The subjects in this study were 10 grade V students. The data were collected through interviews, questionnaires, and validity assessments from material experts, language experts, media experts, as well as a questionnaire of students’ responses. The result of this research was a fun thinkers book learning media consisting of two components: a book and a frame. The feasibility of the media was obtained from the assessments of the experts, namely media experts, material experts, language experts, and students’ responses, with average percentages of 90.8%, 97.5%, 81.82%, and 82.23%, respectively. Based on these results, it was concluded that the fun thinkers book learning media was feasible to be used as a learning media on the topic of “Peristiwa alam yang terjadi di Indonesia.”